Vasorelaxant Activities and its Underlying Mechanisms of Magnolia Volatile Oil on Rat Thoracic Aorta Based on Network Pharmacology - Xu, Jin-Feng; Xia, Jia; Wan, Yan; Yang, Yu; Wu, Jiao-Jiao; Peng, Cheng; Ao, Hui (Frontiers in Pharmacology, 2022)
Objective Magnolia volatile oil(MVO) is a mixture mainly containing eucalyliol and its isomers. This study was to investigate the vasorelaxant effects and the underlying mechanism of MVO in rat thoracic aortas. Method The present study combined gas chromatography-mass spectrometry (GC-MS) and network pharmacology analysis with in vitro experiments to clarify the mechanisms of MVO against vessel contraction. A compound-target(C-T) network, compound-target-disease(C-T-D) network, protein-protein interaction (PPI) network, compound-target-pathway(C-T-P) network, gene ontology and pathway enrichment for hypertension were applied to identify the potential active compounds, drug targets and pathways. Additionally, the thoracic aortic rings with or without endothelium were prepared to explore the underlying mechanisms. The roles of the PI3K-Akt-NO pathways, neuroreceptors, K+ channels and Ca2+ channels on the vasorelaxant effects of MVO were evaluated through the rat thoracic aortic rings. Results A total of 29 compounds were found in MVO, which were identified by GC-MS, of which 21 compounds with content of more than 0.1% were selected for further analysis. The network pharmacology research predicted that beta-caryophyllene, palmitic acid and (+)-β-selinene might act as the effective ingredients of MVO for the treatment of hypertension. Several hot targets, main involving TNF, CHRM1, ACE, IL10, PTGS2, REN and F2 and pivotal pathways, such as the neuroactive ligand-receptor interaction, the calcium signaling pathway and the PI3K-Akt signaling were responsible for the vasorelaxant effect of MVO. As expected, MVO exerted a vasorelaxant effect on the aortic rings pre-contracted by KCl and phenylephrine (PHE) in endothelium-dependent and non-endothelium-dependent manners. Importantly, pre-incubation with indomethacin(Indo), N-nitro-L-arginine methyl ester(L-NAME), methylene blue(MB), wortmannin and atropine sulfate as well as 4-aminopyridione(4-AP) diminished MVO-induced vasorelaxation, suggesting that the activation of PI3K-Akt-NO pathway and KV channel were involved in the vasorelaxant effect of MVO, which were consistent with the results of KEGG. Additionally, MVO could significantly inhibit Ca2+ influx resulting in contraction of aortic rings, revealing that the inhibition of the calcium signaling pathway exactly participated in the vasorelaxant activity of MVO as predicted by network pharmacology.